ANALISIS EFEKTIVITAS BIAYA KEMOTERAPI PADA PASIEN KANKER PAYUDARA DI RSPAD GATOT SOEBROTO JAKARTA - Lili Musnelina; Jenny Pontoan; Clara Jesica Martin (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
Breast cancer is a disease of malignant neoplasm which is an abnormal growth of tissue that is different from the surrounding tissue. Various used of chemotherapy in the process of achieving management in cancer that causes the use of benefits and costs. This study aims to determine a more effective therapy in breast cancer patients at RSPAD Gatot Soebroto in 2017. This study was non experimental with comparative study into two group chemotherapy is single group (chemotherapy bondronat) and combination group (chemotherapy doxorubicin-paclitaxel). This study use secondary data from medical records patients on retrospectively. The results showed a decrease in the scale of single chemotherapy (Bondronat) was 82,61% with an average direct medical cost of IDR 9,3 million where as in combination chemotherapy (Doxorubicin-Paclitaxel) 95,65% with an average direct medical cost of IDR 7,6 million. The ACER value in single chemotherapy was IDR 11,3 million and combination chemotherapy was IDR 7,9 million. The ICER value in the two treatment groups was IDR 13,5 million. The conclusion is the combination of chemotherapy of Doxorubicin-Paclitaxel is the most cost-effective than Bondronate single chemotherapy.